KONVERGENSI PENDAPATAN ANTAR KABUPATEN/KOTA DI KEPULAUAN RIAU - Syafriyani, Mutia; Yeni, Isra (Universitas Negeri Padang, 2025)
This research aims to analyze the extent of convergence among districts and cities in the Riau Islands Province. The data used is sourced from the BPS during the period from 2019 to 2023, involving seven district/city areas. This convergence approach aims to determine whether regions with lagging economies can catch up with more economically advanced areas. Sigma convergence is analyzed by looking at the coefficient of variation of GDP per capita, while beta convergence is tested through panel data regression. The results of the study indicate that both sigma and beta convergence occur in this area. In addition, the Domestic Investment (PMDN) variable has a positive effect on per capita income, although the effect is not significant. Conversely, the Open Unemployment Rate variable has a significant negative effect on per capita income.